2021
DOI: 10.52586/4966
|View full text |Cite
|
Sign up to set email alerts
|

Foliar pathogen-induced assemblage of beneficial rhizosphere consortia increases plant defense against Setosphaeria turcica

Lin Zhu,
Songhua Wang,
Haiming Duan
et al.

Abstract: Background: Foliar pathogen infection can induce the enrichment of beneficial microbial consortia in plant rhizosphere, but the mechanism for enhanced plant resistance is unclear. Methods: We investigated the effects of foliar pathogen infection on bacterial communities in maize rhizosphere using high throughput sequencing. Results: Maize plants grown in non-sterilized soils displayed stronger defense against the foliar pathogen Setosphaeria turcica than those in sterilized soils. Foliar pathogen infection fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…Our study found that pathogen-mediated P. heterophylla enriched Pseudomonas in rhizospheric soil and participated in decreasing the incidence of FW. This result is consistent with studies conducted with maize ( Zhu et al, 2021 ), barley ( Schreiner et al, 2010 ; Dudenhffer et al, 2016 ), wheat ( Landa et al, 2002 ), pea ( Landa et al, 2002 ), carnations ( Lemanceau et al, 1992 ), and Panax notoginseng ( Zhang et al, 2020b ). In addition, Pseudomonas was also mediated by pathogens such as Setosphaeria turcica , Gaeumannomyces gramini , and Fusarium spp.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study found that pathogen-mediated P. heterophylla enriched Pseudomonas in rhizospheric soil and participated in decreasing the incidence of FW. This result is consistent with studies conducted with maize ( Zhu et al, 2021 ), barley ( Schreiner et al, 2010 ; Dudenhffer et al, 2016 ), wheat ( Landa et al, 2002 ), pea ( Landa et al, 2002 ), carnations ( Lemanceau et al, 1992 ), and Panax notoginseng ( Zhang et al, 2020b ). In addition, Pseudomonas was also mediated by pathogens such as Setosphaeria turcica , Gaeumannomyces gramini , and Fusarium spp.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Pseudomonas was also mediated by pathogens such as Setosphaeria turcica , Gaeumannomyces gramini , and Fusarium spp. ( Lemanceau et al, 1992 ; Landa et al, 2002 ; Zhang et al, 2020b ; Zhu et al, 2021 ). Furthermore, Pseudomonas was induced by F. oxysporum to colonize on the tuberous roots, which was similar to the results of a previous study showing that leaf pathogens can mediate the colonization of Pseudomonas on Arabidopsis roots ( Léon-Kloosterziel et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%